Motivations and Land-Use Intentions of Nonindustrial Private Forest Landowners: Comparing Inheritors to Noninheritors - Indrajit Majumdar; David Laband; Lawrence Teeter; Brett Butler (Forest Science, 2009)
The documented importance of intergenerational human capital transfers in agriculture generally gives us reason to suspect that such transfers may be important in a forestry context and that there may be important implied differences between first-generation woodland owners and multigeneration woodland owners with respect to their motivations and future intentions. In turn, knowledge of the motivations and intentions of nonindustrial private landowners may be extremely important because such knowledge may be vital in terms of our ability to predict future timber supply and the availability of nontimber amenities. Also, the effectiveness of public policies targeting nonindustrial private forest landowners may depend critically on their motivations and intentions. In this article, we analyzed 8,373 responses to the National Woodland Owner Survey to compare characteristics, motivations, and intentions of multigeneration forest landowners against those of single-generation forest landowners. In brief, we found there were significant differences in their motivations and management behavior; inheritors are more active forest managers and manage for both timber and nontimber forest products more aggressively than noninheritors who typically value esthetics, privacy, protection of biodiversity, and nonhunting recreation.

Characterizing Family Forest Owners: A Cluster Analysis Approach - Indrajit Majumdar; Lawrence Teeter; Brett Butler (Forest Science, 2008)
For policy implementation to promote better stewardship on family forestlands, it is necessary to understand what motivates landowners. This study characterizes family forest owners in Alabama, Georgia, and South Carolina, based on their feelings about forest stewardship and their stated reasons for owning forestland. Multivariate cluster analysis suggests that family forest owners are, in fact, a diverse set of owners who can be grouped into three attitudinal types, namely, multiple-objective, nontimber, and timber. The multiple-objective ownership type was found to be the largest group (49.1% of respondents) with almost half the family forest owners in the sample population belonging to this category. Owners belonging to the timber cluster (29.4%) indicated only timber management and land investment as strong motivating factors behind their forestland ownership, whereas owners belonging to the nontimber cluster (21.5%) value the nonconsumptive uses of their forestland such as aesthetic values, biodiversity, recreation, and privacy.

Modeling Pulpwood Trade within the United States South - Maksym Polyakov; Lawrence Teeter (Forest Science, 2007)
Interregional trade of roundwood products is an important factor of regional roundwood markets. Until now, regional and subregional forest sector models did not account for the spatial aspects of roundwood markets. This article explores ways to model interregional trade of roundwood products. It compares the performance of different specifications of a gravity model (the model widely used in the analysis of international trade) and a fixed gravity coefficient model (common in regional input-output analysis) to forecast pulpwood trade between the states of the United States South. The gravity model estimated using nonlinear least-squares with fixed effects (NLS FEM) and the fixed gravity coefficient model (FGCM) showed the best results. Another important result of this study is the finding that the fixed gravity coefficients for pulpwood trade in the United States South are temporally stable. This suggests the possibility of using the FGCM for modeling roundwood trade in the absence of time series data.

Projecting Timber Inventory at the Product Level - Lawrence Teeter; Xiaoping Zhou (Forest Science, 1999)
Current timber inventory projections generally lack information on inventory by product classes. Most models available for inventory projection and linked to supply analyses are limited to projecting aggregate softwood and hardwood. The research presented describes a methodology for distributing the volume on each FIA (USDA Forest Service Forest Inventory and Analysis) survey plot to product classes given a type characterization, volume, and average dbh (diameter at breast height, 1.37 m above average ground level) for the plot. A multinomial logit model was developed to estimate sets of product proportion functions to distribute plot volumes by product class for each forest type and size class. A discussion of the performance of the model using Alabama and Mississippi FIA plot level data is provided. For. Sci. 45(1):226-231.

Relationships Between Landscape Characteristics and Nonpoint Source Pollution Inputs to Coastal Estuaries - PRAKASH BASNYAT , LAWRENCE D. TEETER; KATHRYN M. FLYNN; B. GRAEME LOCKABY (Environmental Management, 1999)